Roh Kudus, Napas Sang Rentan dan Marginal: Pandemi Covid-19 dan Orang Miskin di Indonesia - Timotius Verdino (STFT Jakarta, Indonesia, 2020)
This article is a contextual theology regarding the poor in Indonesia in the Covid-19 Pandemic situation. I will start this paper by presenting the poverty situation and poor people’s experience of injustice in Indonesia during the Covid-19 Pandemic. Then, I will discuss the biblical review of God’s will for justice for the poor and discuss the perspective of liberation theology on poverty by Aloysius Pieris. After that, both discussions will be placed in the conversation with John 20:22. In the end, this paper will conclude a contextual theological construction of the Holy Spirit, as the breath of the vulnerable and the marginalized people who seek for justice in the Covid-19 Pandemic situation.